Politeness Strategies in the Hempang Batang Pantun: The Traditional Wedding Ceremony Sequence in Resam Melayu Deli - Elvi, Syahrin (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Politeness is a phenomenon that defines the appropriateness and one’s conformity with the required social and linguistic norms in a speech community. This “key of interaction” seems to be an important device in order to carry out successful communication. Brown & Levinson (1987) argue that politeness means acting so as to take account of the feelings of others and includes both those actions concerned with “positive face” (the wish to be approved) and “negative face” (the wish to be unimpeded, free from imposition, or left alone). Face can be lost, maintained, or enhanced. Thus, politeness implies the act of maintaining face. One can lose his face when behaving in a way which is not consistent with the expected behavior associated with one’s face. For example, a Telangkat Adat in Malay tradition is supposed to talk and behave wisely and respectfully in accordance with his role in the community. He would lose his face, once he behaves differently or violates social norms.